(untitled) (XXI Century. Spanish Literature and Culture, 2008)
A poem doesn’t exhaust itself in the silent world of our I: its reading is a meeting of voices, an echo of traditions, a pact of complicity of the author and the one who listens to him, of the reader with their I and, ¨the they¨ that reside in its intimate world. Without the pretension of giving precepts and regulatory instructions, Carlos Marzal proposes in this article a reading of the poem separated from the cathartic pathos or declamatory tone. The reader, with the sobriety of its own personal emotive nature, forges in each one of its words the echo of a recited reading among company, a production of man with himself and with humanity. Poetry, musicality, and recitation interweave in the poem as a biological necessity of the human language.